Upaya Mendukung Keberhasilan Implementasi Rekam Medis Elektronik Melalui Digitalisasi Rekam Medis - Kori Puspita Ningsih; Endang Purwanti; Suryo Nugroho Markus; Sugeng Santoso; Husin Husin; Muhammad Zaini (Poltekkes Kemenkes Surakarta, 2022)
Background: The development of the digital era makes routine and quality data integration an essential component in realizing digital transformation. One data that must be maintained is the Electronic Medical Record (RME). Wates Hospital is currently testing the implementation of RME and requires technical assistance in digitizing medical records in paper to electronic form. Digitization is necessary to ensure the patient's medical history information continuity. The digitization of medical records is expected to support the successful implementation of RME in Wates Hospital. Methods: Solutions are carried out in solving partner problems through training and science and technology substitution. Training activities are carried out by providing counseling, demonstrations, and training to operate scanner equipment. The substitution of science and technology in this PKM is by offering new science and technology to digitize medical records to replace the old science and technology mastery. Results: The activity is divided into 3 stages, starting with providing training related to the procedure for digitizing medical records, then assisting officers during the digitization process of medical records, and ending with accompanying the reflection process to evaluate the success of digitizing medical records. Pre-test and post-test showed an increase in the